Jet-Like Appearance in Angiography as a Predictive Image Marker for the Occlusion of Intracranial Atherosclerotic Stenosis - Jin, Xing; Shi, Feina; Chen, Yigang; Zheng, Xu; Zhang, Jinhua (Frontiers in Neurology, 2020)
Introduction: Identifying intracranial atherosclerotic stenosis-related occlusion (ICAS-O) in acute ischemic stroke has important clinical significance. Correct identification would help operators devise an optimal recanalization strategy. However, it is often hard to make accurate judgments in emergency situations before thrombectomy. Here, we propose a new image marker for ICAS-O based on the appearance of occluded vessels on baseline digital subtraction angiography. Materials and Methods: We retrospectively reviewed patients with acute ischemic stroke who underwent endovascular therapy from August 2017 to February 2020 at our center. ICAS-O was identified by residual focal stenosis at occluded vessels after successful recanalization. The jet-like appearance was defined as appearance of pencil-tip-like or line-linked contrast filling of the occlusion edge. A non-jet-like appearance was defined as appearance of convex, concave, or flat edge contrast filling. The proportion of jet-like appearance in different occlusion etiologies and occluded vessels was determined. The diagnostic value of jet-like appearance for ICAS-O was assessed. Results: A total of 164 patients diagnosed with ICAS-O were enrolled. Jet-like appearance was detected in 34 (20.7%) patients with younger age (68.0 ± 11.9 years vs. 62.7 ± 10.2, p = 0.019), patients with lower baseline NIHSS scores (16.6 ± 7.1 vs. 12.4 ± 6.5, p = 0.002) and patients with more past stroke or transit ischemic events (31.4 vs. 13.2%, p = 0.011). ICAS-O rate was higher in the jet-like appearance group (82.9 vs. 8.5%, p < 0.001), and rescue methods were more frequently used (74.3 vs. 12.4%, p < 0.001). Jet-like appearance was mostly found at the origin of the middle cerebral artery (MCA) (44.1%), followed by the first segment trunk of MCA (20.6%) and internal carotid artery (ICA) supraclinoid (11.8%). Logistic regression showed that jet-like appearance was independently associated with ICAS-O [OR 180.813, 95% CI (17.966, 1,819.733), p < 0.001]. The sensitivity, specificity, and accuracy values for predicting ICAS-O was 96, 78, and 83%. Conclusion: The jet-like appearance on the angiogram was an image marker for ICAS-O, with relatively high sensitivity and specificity, which could help operators predict underlying intracranial atherosclerotic stenosis in a timely manner and choose the optimal intervention strategy during endovascular therapy.